Complete and complete integral convergence for weighted sums of arrays of rowwise widely negative dependent random variables under the sub-linear expectations. Issue 4 (16th February 2023) - Lu, Dawei; Meng, Yao
Abstract: In this article, we study complete and complete integral convergence theorems for weighted sums of arrays of rowwise widely negative dependent random variables under the sub-linear expectations. The presented results are Baum-Katz type theorems that extend the corresponding results in classical probability space to the case of sub-linear expectation space.